Needs–supplies fit and behavioral outcomes: The mediating role of organizational identification. (26th July 2016) - Travaglianti, Fabrice; Babic, Audrey; Pepermans, Roland; Hansez, Isabelle
Abstract: While it is well known that person–organization fit is an important antecedent of behavioral outcomes, little is known about needs–supplies fit in this relationship. In this way, we first want to extend our knowledge about defining and assessing work-related needs derived from employment quality indicators as the basis for needs–supplies fit. Second, following the Cognitive and Affective Personality System theory, we test the mediating role of organizational identification to better understand how needs–supplies fit is related to task performance and organizational citizenship behaviors. Data were collected in two companies: sample 1 ( N =525) and sample 2 ( N =525). Results show (a) that a specific needs–supplies fit perception (i.e., based on 12 work-related needs derived from employment quality indicators) is positively related to a global needs–supplies fit perception (i.e., based on an overall job perception), suggesting that needs–supplies fit may be a multidimensional concept and (b) the full mediating role of organizational identification in the relationship between needs–supplies fit and performance measures.